2015
DOI: 10.3747/pdi.2013.00156
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Monitoring Vancomycin Levels in Patients with Peritoneal Dialysis-Associated Peritonitis

Abstract: The clinical outcomes of gram-positive and culture-negative peritonitis episodes are not associated with either the frequency or levels of serum vancomycin measurements in the first week of treatment when vancomycin is dosed according to International Society for Peritoneal Dialysis (ISPD) Guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 15 publications
0
23
0
1
Order By: Relevance
“…A randomized controlled trial in children found that intermittent dosing of vancomycin is as efficacious as continuous dosing ( 311 ). The role of monitoring serum vancomycin levels is controversial ( 284 , 312 ). In general, a dosing interval of every 4 to 5 days would keep serum trough levels above 15 μg/mL, but there is substantial inter-individual variability ( 284 , 304 ).…”
Section: Initial Presentation and Management Of Peritonitismentioning
confidence: 99%
“…A randomized controlled trial in children found that intermittent dosing of vancomycin is as efficacious as continuous dosing ( 311 ). The role of monitoring serum vancomycin levels is controversial ( 284 , 312 ). In general, a dosing interval of every 4 to 5 days would keep serum trough levels above 15 μg/mL, but there is substantial inter-individual variability ( 284 , 304 ).…”
Section: Initial Presentation and Management Of Peritonitismentioning
confidence: 99%
“…Clinical outcomes of gram‐positive and culture‐negative peritonitis were not associated with either the frequency or levels of serum vancomycin measurements in the first week of treatment when vancomycin is dosed according to International Society for Peritoneal Dialysis …”
Section: Therapeutic Drug Monitoringmentioning
confidence: 98%
“…Given equivalent TDM costs and the lack of a clear clinical benefit, the role of CI remains to be defined, in spite of practical and theoretical advantages, particularly in burn patients Patients receiving ambulatory peritoneal dialysisThe JPN guideline summarizes evidence and presents recommendations for this subpopulation (Table ).Clinical outcomes of gram‐positive and culture‐negative peritonitis were not associated with either the frequency or levels of serum vancomycin measurements in the first week of treatment when vancomycin is dosed according to International Society for Peritoneal Dialysis describes the PPK models developed for this subpopulation. …”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%
“…On the other hand, data from a single-center study involving 34 PD patients experiencing PD-related peritonitis showed no relationship between plasma vancomycin levels measured during the first week and PD-related peritonitis outcomes. 42 Here, CAPD was reportedly the most frequent modality (80%) used with an average residual creatinine clearance of 2.8 mL/min/1.73 m2. Vancomycin was dosed based on ISPD recommendations and plasma levels were maintained above 15 mg/L.…”
Section: Tdm and Pharmacodynamic Responsementioning
confidence: 82%